Handbook of environmental fluid dynamics - Fernando, H. J. S. (Taylor & Francis, 2013)
"With major implications for applied physics, engineering, and the natural and social sciences, the rapidly growing area of environmental fluid dynamics focuses on the interactions of human activities, environment, and fluid motion. A landmark for the field, this two-volume Handbook of Environmental Fluid Dynamics presents the basic principles, fundamental flow processes, modeling techniques, and measurement methods used in the study of environmental motions. It also offers critical discussions of environmental sustainability related to engineering